Bayesian framework for building gene regulatory networks including delays - Iti Chaturvedi (2013)
Any biological activity is due to several genes regulating one another in a gene regulatory network (GRN). GRN are causal models where activation of one gene could cause another gene to be activated or inhibited. Dynamic Bayesian networks (DBN) are being widely used to model GRN because of their ability to capture complex regulatory interactions among genes. DBN are presumed to be of first-order such that gene expression at a particular time point is only dependant on the previous time point. However, regulatory events are inherently asynchronous and transpire at different times, and involve delays. In order to account for delays in GRN, we propose higher-order DBN.